Impact of Financial Literacy on Vietnamese Students’ Spending Management - Anh, Khuc The; Vinh, Tran Tuan (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
The study was carried out to evaluate the impact of financial literacy by considering the influence of three components: Financial Attitude, Financial Knowledge and Financial Behavior on students’ spending management. The article used a combination of qualitative and quantitative research (through Structural Equation Modeling - SEM) to evaluate. The results showed that financial knowledge and financial attitude do not influence students’ spending management, while financial behavior and influence of parents are statistically significant factors. Primarily, financial behavior has the most prominent influence. From the research results, the author has made some policy implications for relevant agencies to improve the influence of parents on children and to improve students' financial behaviour.